Quality of life of children with poor school performance: association with hearing abilities and behavioral issues - Rezende, Bárbara Antunes; Lemos, Stela Maris Aguiar; Medeiros, Adriane Mesquita de (Arquivos de Neuro-Psiquiatria, 2019)
The aim of the present study was to investigate the quality of life of children with poor school performance and its association with behavioral aspects and hearing abilities.Methods: This cross-sectional observational study, developed in a town in the state of Minas Gerais, Brazil, investigated a random sample of public school children, aged 7-12 years old, who performed poorly in school and received specialized educational assistance. The study comprised two stages: 1) collection of data from parents on their children's health, educational, and socioeconomic profile, and from the Strengths and Difficulties Questionnaire; 2) administration of a quality of life evaluation scale to the schoolchildren. For the assessment of auditory function, transient otoacoustic emissions were used and auditory processing was tested. The following tests were used: verbal sequential memory, nonverbal sequential memory, sound localization, dichotic digits, duration pattern test (flute) and random gap detection. The collected data were analyzed using Excel and STATA 11.0 software. Quality of life was considered the response variable. The explanatory variables were grouped for univariate and multivariate logistic regression analysis with the level of significance set at 5%.Results: A statistically significant association was found between impaired quality of life, altered pro-social behavior, and the absence of parental complaints about the children's written language development.Conclusions: Quality of life is impaired in children with poor school performance. The lack of parental complaints about written language and changes in social behavior increased the likelihood of a child having a poor quality of life.
Keywords: Quality of life; underachievement; child behavior; hearing tests; child